'I Want to Play Alone': Assessment and Correlates of Self‐Reported Preference for Solitary Play in Young Children. Issue 3 (26th February 2014) - Coplan, Robert J.; Ooi, Laura L.; Rose‐Krasnor, Linda; Nocita, Gabriella; Schmidt, Louis A.; Coplan, Robert J.
<x xml:space="preserve">Abstract</x> The goal of this study was to develop and validate an interview assessment of preference for solitary activities for use with young children. We also tested the postulation that negative peer experiences would heighten preference for solitude, particularly among young shy children. Participants were N = 193 children (87 boys, 106 girls; Mage = 65.76 mos, SD = 12.68) attending preschools and elementary schools (kindergarten, grade 1) located in south‐eastern Ontario, Canada. Self‐reported preference for solitude was measured with the newly developed Preference for Solitary Play Interview (PSPI). Children also reported their perceived peer acceptance. Mothers provided ratings of children's social withdrawal (shyness and unsociability) and social engagement outside of school, and teachers assessed children's socio‐emotional functioning at school. Among the results, the newly developed PSPI displayed good psychometric properties and evidence of construct/convergent validity. For example, preference for solitary play was positively related to indices of social withdrawal, and negatively associated with social engagement, prosocial behaviour, and perceived peer acceptance. In addition, peer exclusion was found to exacerbate the association between shyness and preference for solitary play. Results are discussed in terms of the assessment and implications of preference for solitude in early childhood. Copyright © 2014 John Wiley & Sons, Ltd.